Gambaran Umum Deteksi Dini CA Serviks Dengan Pap Smear pada Pasangan Usia Subur di Puskesmas Kesu - Yenni Yenni; Andi Tenri Angka (JURNAL KEPERAWATAN SISTHANA, 2019)
A Pap smear is an attempt to take fluid from the cervix to examine the presence of abnormalities in the cells around the cervix. In this examination, it can usually be determined whether the cells in the mouth of the uterus are still normal, have changed into cancer, or have become cancer cells. Apart from that, inflammation and infection of the cervix can be determined from this examination. The aim of the research is to find out the general picture of early detection of cervical CA with pap smears in couples of childbearing age at the Kesu Health Center. This research was carried out by the Kesu Health Center. The method in this research uses descriptive analytics by taking a sample of 100 centers, with an accidental sampling technique, namely taking samples by taking into account the researchers' considerations. The data used in the research is primary data with the variables studied namely early detection of cervical CA with pap smears. Based on 100 respondents who had good knowledge, 47 people (47%), had sufficient knowledge, 49 respondents (49%) and had sufficient knowledge, 4 people (4%). Based on 100 respondents who received information sources, 40 respondents (40%) from print, electronic and non-media media did not know where to get pap smears and 60 respondents (60%) who did not get information from print, electronic and non-media media did not know where to get pap smears. Based on 100 respondents, all of them did not know where to get a pap smear. The conclusion is that there are more PUS who have sufficient knowledge and less and do not know where to check pap smears. It is hoped that the midwives at the Kesu' Community Health Center will further increase their education to couples of childbearing age so that they are willing to carry out early detection examinations for cervical Ca.